The Role of The Waqf Bank for Students (Case Study of the Amal Jariyah Waqf Bank and the STF of UIN Syahid Jakarta) - Syahputra, Angga; Khairina, Khalish; Jailani, Munawar Rizki (Universitas Islam Negeri Raden Intan Lampung, 2022)
Students have various funding problems before and after the Covid-19 pandemic. 2018 data from the Ministry of Education shows that there are 8,043,480 students in Indonesia. In the same year, there were 3% of students who dropped out of college due to various reasons, including the economy. The government itself has made various efforts to overcome this problem. However, in practice, many students do not feel the assistance provided by the government. For this reason, the campus certainly must not let go and must provide solutions for students to stay in college. This research will look at the right waqf bank model as one of the solutions that can be done by the campus. The researcher uses descriptive qualitative research using secondary data in examining the Amal Jariyah Student Waqf Bank and STF UIN Syahid Jakarta as a waqf bank model that can be developed by each campus. The results of this study indicate that the Amal Jariyah Student Waqf Bank and STF UIN Syahid Jakarta are the right models for other campuses to establish waqf banks. These two waqf bank models have proven to be successful in providing great contributions not only to students but also to the wider community.